Respostas fisiológicas de physalis angulata l. cultivadas em doses de molibdênio em sistema hidropônico - Fonseca, Josandra Souza Teles (2021)
Studies aimed at the development of plants associated with the effects of the application of molybdenum (Mo), an essential micronutrient with an important role in development and several biochemical processes, is an important strategy that can offer benefits for nutritional management in crops such as Physalis angulata L. Camapú is a herbaceous plant with a neotropical distribution and presents fruits with nutraceutical properties and the cultivation management is not yet fully defined. To evaluate the responses of Physalis angulata cultivated in doses of molybdenum in hydroponic culture. The trial was conducted in hydroponic cultivation in a controlled environment in the Horto Florestal belonging to the State University of Feira de Santana. Five doses of Mo were tested (0, 0.005, 0.01, 0.015 and 0.02 mg dm-3 of H2MoO*4H2O), considering a completely randomized design and twelve replications with five plants each plot. The chlorophyll content was evaluated in the leaves and the gas exchange parameters were obtained: internal carbon, stomatal conductance, carbon assimilation, transpiration and water use efficiency. It was also measured the nitrate reductase activity, the quantification of the total protein content and the production of dry matter of leaves, roots, stems as well as the shoot root ratio. The supply of Mo (0.02 mg dm-3) provided phytomass gains, a variable related to the total mass of the plants and in the content of chlorophyll a and total. The activity of the nitrate reductase enzyme in leaves and roots was stimulated by Mo supplementation, with the highest activity in the roots. The photosynthetic rate (0.010 mg dm-3) and the water use efficiency (0.015 mg dm-3) were favored by the increase in Mo doses. The results showed that the fertilization with molybdenum provided positive effects on the phytomass gain and on the levels of photosynthetic pigments of P. angulata plants in hydroponic cultivation, as well as on the photosynthetic rate and the efficiency of water use.